THE ROLE OF PUBLIC RELANTIONS PT. GARUDA TBK INDONESIA IN MAINTAINING CORPORATE IMAGE DURING THE COVID 19 PANDEMIC - Renaldo Aswansyah Putera; Aminah Swarnawati (Sean Institute, 2023)
A crisis can be called a public relations crisis if the crisis results in damage to the image of the company or organization in the public eye. The rise of coverage in the mass media regarding news about air transportation services will have an impact on the public who will judge the image of a company. The purpose of this study is to find out how the role of public relations in maintaining the image of PT Garuda Indonesia Tbk; To understand the crisis that occurred at PT Garuda Indonesia Tbk. This study uses a qualitative methodology using the theory of Timothy Coombs (2006) Situational Crisis Communication Theory . The results of this study are that Garuda Indonesia's debt is very large due to changes in the recognition of obligations where the operational lease (aircraft lease) was previously recorded as an opex so debt besides that there is no good communication with stakeholders in this case creditors or investors. The conclusion of this study is the inability to manage the crisis that caused this airline to experience multiple losses due to the series of crises that followed. If only Garuda Indonesia could manage its finances properly and communication between divisions/departments was well established, this could be minimized. Going forward, Garuda Indonesia's management needs to properly improve their internal and external communications, especially when facing a crisis related to investor relations.